2019
DOI: 10.1111/ajt.15232
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial damage–associated molecular patterns released by lung transplants are associated with primary graft dysfunction

Abstract: Primary graft dysfunction (PGD) is a major limitation in short-and long-term lung transplant survival. Recent work has shown that mitochondrial damage-associated molecular patterns (mtDAMPs) can promote solid organ injury, but whether they contribute to PGD severity remains unclear. We quantitated circulating plasma mitochondrial DNA (mtDNA) in 62 patients, before lung transplantation and shortly after arrival to the intensive care unit. Although all recipients released mtDNA, high levels were associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 53 publications
(95 reference statements)
0
38
0
Order By: Relevance
“…The reasons for this incongruence are not clear. However, when compared to MT-CYTB, we generally detected lower copy numbers for MT-COX3, suggesting the possibility that this part of mitochondria genome is more intrinsically unstable when exposed to plasma (Scozzi et al, 2019).…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…The reasons for this incongruence are not clear. However, when compared to MT-CYTB, we generally detected lower copy numbers for MT-COX3, suggesting the possibility that this part of mitochondria genome is more intrinsically unstable when exposed to plasma (Scozzi et al, 2019).…”
Section: Discussionmentioning
confidence: 71%
“…Finally, MT DAMPs, unlike other inflammatory markers linked to poor outcomes of COVID-19 afflicted patients, have been reported to directly cause acute pulmonary dysfunction and tissue damage (Lee et al, 2017). Administration of MT DAMPs into the blood stream or pulmonary airways of rodents promotes acute lung injury mediated by neutrophil chemotaxis and reactive oxygen species generation to mitochondrial formylated peptides (Hauser et al, 2010;Scozzi et al, 2019). In these studies, the formylated peptide receptor-1 inhibitor cyclosporine H was shown to inhibit MT DAMP-mediated acute lung injury.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Release of mitochondrial content exposes transplant recipients to donor-derived proteins and mtDNA --a very potent DAMP (33,34). Scozzi and colleagues, as well as others (35), have described the association of circulating mtDNA with severe primary graft dysfunction after lung transplantation and proposed that the graft injury is coupled with neutrophil trafficking (36). We demonstrate that mtDNA peptide variants elicit allo-specific immune responses, which may potentially contribute to allograft rejection.…”
Section: Discussionmentioning
confidence: 56%